Lender Monitoring and the Efficacy of Managerial Risk-Taking Incentives - Hong, Hyun A.; Ryou, Ji Woo; Srivastava, Anup (The Accounting Review, 2021)
ABSTRACT Firms provide convexity in managers' compensation plans (vega) to induce risk-averse managers to pursue risky, positive net present value projects. The resulting alignment of managers' and shareholders' incentives creates conflicts with lenders, who face an increased risk of default when managers pursue risky investments. We hypothesize that lenders would respond by stepping up their monitoring and threatening foreclosure to inhibit managers from acting on their vega incentives. Strong lender monitoring should, thus, reduce the efficacy of vega incentives. We test this hypothesis in a unique setting, where lenders purchase credit insurance, reduce their exposure to downside risk, and lower their monitoring. Afterward, we find a stronger association between vega incentives and the firms' risky investments. We contribute to the literature by showing that strong lender monitoring reduces the effectiveness of vega incentives and, thus, of the compensation mechanisms that boards of directors put in place to resolve manager-shareholder conflicts. JEL Classifications: G32; G33; M41; M48.